2015
DOI: 10.1021/acs.jafc.5b02131
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Bioconversion of Winery and Olive Mill Waste Mixtures into Lignocellulolytic Enzymes and Animal Feed byAspergillus uvarumUsing a Packed-Bed Bioreactor

Abstract: Wineries and olive oil industries are dominant agro-industrial activities in southern European regions. Olive pomace, exhausted grape marc, and vine shoot trimmings are lignocellulosic residues generated by these industries, which could be valued biotechnologically. In the present work these residues were used as substrate to produce cellulases and xylanases through solid-state fermentation using Aspergillus uvarum MUM 08.01. For that, two factorial designs (3(2)) were first planned to optimize substrate compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 43 publications
(83 reference statements)
3
48
0
1
Order By: Relevance
“…The enzyme activities achieved by SSF with low cost nutrients (cellulase activity: 9.99 ± 1.39 U/g; xylanase activity: 19.44 ± 3.85 U/g) were lower than the activities achieved using commercial nutrients. Salgado et al (2015) observed a positive effect of urea and vinasses as nutrient supplement in SSF carried out with mixtures of olive pomace, exhausted grape marc and vine trimming shoots.…”
Section: Effect Of Nutrients Supplementationmentioning
confidence: 88%
See 4 more Smart Citations
“…The enzyme activities achieved by SSF with low cost nutrients (cellulase activity: 9.99 ± 1.39 U/g; xylanase activity: 19.44 ± 3.85 U/g) were lower than the activities achieved using commercial nutrients. Salgado et al (2015) observed a positive effect of urea and vinasses as nutrient supplement in SSF carried out with mixtures of olive pomace, exhausted grape marc and vine trimming shoots.…”
Section: Effect Of Nutrients Supplementationmentioning
confidence: 88%
“…According to Giannoutsou et al (2012) this slight increase may be the result of the degradation of polyphenols to smaller phenolic compounds that may be an indication that the microorganism could use the specific substrate for its growth. Salgado et al (2015) also studied the course of the compounds over fermentation time and proved the depletion of the sugars, the increase of the proteins percentage from 8.47% to 17.98% after 6 days of fermentation and the degradation of phenol compounds, obtaining 28.32% reduction of phenols after 10 days of fermentation. The decrease in activity with increasing incubation time may be due to the production of by products resulting from microbial metabolism, as well as nutrient depletion, inhibiting fungal growth and enzyme formation (Shafique et al, 2009).…”
Section: Study Of Enzymes Production Kineticsmentioning
confidence: 99%
See 3 more Smart Citations